Effect of Metformin on Breast Density in Overweight/Obese Premenopausal Women - Leng W (Dove Medical Press, 2021)
Weiling Leng,1 Danlan Pu,2 Juan Jiang,2 Xiaotian Lei,1 Qinan Wu,3,* Bing Chen1,* 1Endocrinology Department, The First Affiliated Hospital of the Third Military Medical University (Army Medical University), Chongqing, People’s Republic of China; 2Endocrinology and Nephrology Department, Chongqing University Cancer Hospital and Chongqing Cancer Institute and Chongqing Cancer Hospital, Chongqing, People’s Republic of China; 3Endocrinology Department, Chongqing Medical University Affiliated Dazu Hospital, Dazu District People’s Hospital, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qinan Wu; Bing Chen Email wqn11@126.com; chenbingxnyy@126.comBackground: This study investigated the effects of metformin on breast density in overweight/obese premenopausal women.Methods: Overweight/obese premenopausal women (n=120) were randomly assigned to the metformin or placebo group, and all women received lifestyle interventions. The outcomes included weight, BMI, FPG, FIN, glucose, HOMA-IR, LDL-C, HDL-C, TG, TC, SBP, DBP, FSH, E, AD, and the BIRADS grade, and the incidence of breast cancer was assessed by pathological biopsy and BIRADS grade greater than 4.Results: In total, 120 overweight/obese women completed the 1-year trial. Seven patients had a BIRADS grade greater than 4, including 5 patients who were biopsy positive, in the control group, and 2 patients had a BIRADS grade greater than 4, including 1 patient who was biopsy positive, in the metformin group. Compared with those in the control group, the body weight, BMI, FIN, FPG, HOMA-IR, TC, BIRADS grade and positive pathological biopsy rate in the metformin group were significantly decreased (P< 0.05), while AD was significantly increased (P< 0.05). The correlation analysis indicated that the BIRADS grade was significantly correlated with weight, BMI, FPG, FIN, HOMA-IR, SBP, AD and the positive pathological biopsy rate, and the positive pathological biopsy rate was significantly correlated with weight, BMI, HOMA-IR, SBP, AD and BIRADS grade. The logistic regression analysis revealed that the BIRADS grade was significantly correlated with the positive pathological biopsy rate and AD and that the positive pathological biopsy rate was significantly correlated with the BIRADS grade.Conclusion: As adjunctive therapy, the combination of lifestyle changes and metformin was found to be a safe strategy for improving related metabolic markers and increasing adiponectin. The BIRADS grade was significantly correlated with the positive pathological biopsy rate and AD, and the positive pathological biopsy rate was significantly correlated with the BIRADS grade.Keywords: metformin, breast density, overweight/obese, adiponectin